I smile back [videorecording (DVD)] - Silverman, Sarah; Charles, Josh, 1971-; Sadoski, Thomas, 1976- (Broad Green Pictures, 2016)
Laney is an attractive, intelligent suburban wife and devoted mother of two adorable children. She has the perfect husband who plays basketball with the kids in the driveway, a pristine house, and a shiny SUV for carting the children to their next activity. However, just beneath the facade lie depression and disillusionment that send her careening into a secret world of reckless compulsion. Only very real danger will force her to face the painful root of her destructiveness.